Penyajian Teknik Bernyanyi pada Lagu Le violette Karya Alessandro Scarlatti - Priska Juli Kristine Giawa; Ance Juliet Panggabean; Agustina Helena Samosir (FBS Universitas Negeri Padang, 2022)
This study discusses the presentation of singing techniques in the song Le violette by Alessandro Scarlatti. The singing techniques used in singing the song are posture, breathing, sound production, articulation, intonation, resonance, and dynamics. The author also discusses the characteristics of the song. The distinctive feature of the music that the author brings is the solo vocal work which connects with the expression of falling in love with someone. The author applies it repeatedly until it can be done for quite a long time so that the mastery of Le violette's songs is really mature both in terms of song mastery and mentally, and is ready to be performed.